2016
DOI: 10.1093/ndt/gfw094
|View full text |Cite
|
Sign up to set email alerts
|

Reaccumulation of globotriaosylceramide in podocytes after agalsidase dose reduction in young Fabry patients

Abstract: Partial clearance, reaccumulation and renewed partial clearance of podocyte GL3 deposits in serial kidney biopsies over 8-10 years were seen in parallel with agalsidase dose adjustments. Repeated kidney biopsies may impact therapeutic choices in Fabry disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 25 publications
2
31
0
8
Order By: Relevance
“…We also strongly support that nephrologists in general advocate and strive to maintain their knowledge and hands-on experience regarding the procedure [18,19]. The important role of kidney biopsies in the diagnosis, classification and assessment of therapeutic efficacy in Fabry disease has recently been highlighted in several studies and case series [3,7,12,16,20], as well as in a recent KDIGO conference report [4]. There is increasing evidence that accumulation of Gb3 in podocytes is an early marker of potential progressive Fabry nephropathy, and several studies have shown that prominent histological changes appear far earlier than clinical renal symptoms or albuminuria [21,22].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We also strongly support that nephrologists in general advocate and strive to maintain their knowledge and hands-on experience regarding the procedure [18,19]. The important role of kidney biopsies in the diagnosis, classification and assessment of therapeutic efficacy in Fabry disease has recently been highlighted in several studies and case series [3,7,12,16,20], as well as in a recent KDIGO conference report [4]. There is increasing evidence that accumulation of Gb3 in podocytes is an early marker of potential progressive Fabry nephropathy, and several studies have shown that prominent histological changes appear far earlier than clinical renal symptoms or albuminuria [21,22].…”
Section: Discussionmentioning
confidence: 53%
“…3-5) show the capacity of the stereomicroscopy scoring method to assess differences in the effectiveness of enzyme therapy, the scoring of white deposits was paralleled by similar histologic scorings of Gb3 deposits in the toluidine blue stained sections. The relevance of diagnosing the increase or decrease of podocyte inclusions has previously been shown in case reports and small series, and provides guidance for adjustments in dosing of enzyme replacement therapy [12,16]. Of note, complete regression of white glomerular deposits has been found in patients after long-term agalsidase treatment in parallel with near total regression of histologic scores [12].…”
Section: Discussionmentioning
confidence: 89%
“…As shown in our results, the disease progression was accelerated if ERT patients already had a more severe albuminuria at baseline. Studies suggest that maximal treatment effect in Fabry nephropathy can be achieved at an early stage with normal or almost normal kidney function [11, 35, 36]. Tondel et al have described beneficial effects of ERT detected in kidney biopsies regarding clearance of glomerular endothelial and mesangial cell inclusions in patients with well-preserved renal function [11, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that maximal treatment effect in Fabry nephropathy can be achieved at an early stage with normal or almost normal kidney function [11, 35, 36]. Tondel et al have described beneficial effects of ERT detected in kidney biopsies regarding clearance of glomerular endothelial and mesangial cell inclusions in patients with well-preserved renal function [11, 35]. A recent study by Germain and colleagues showed that less affected individuals with a better preserved kidney function at baseline benefited from ERT, experiencing better renal and cardiovascular outcomes during the observational period [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation